Thanatophoric dysplasia in identical twins. Issue 4 (April 1989) - Young, I D; Patel, I; Lamont, A C
Abstract : Female twins concordant for thanatophoric dysplasia are presented. Monozygosity was confirmed using minisatellite DNA genetic fingerprinting. The evidence supporting new dominant mutations as the likely cause of thanatophoric dysplasia is reviewed.